2020
DOI: 10.20527/jps.v7i2.8731
|View full text |Cite
|
Sign up to set email alerts
|

Penambatan Molekul Kandungan Eurycoma longifolia Jack. (Pasak bumi) terhadap Human Phosphodiesterase 5

Abstract: Pasak bumi sebagai obat tradisional pria telah digunakan oleh masyarakat melayu, khususnya orang Sumatra dan kalimantan, akan tetapi mekanisme secara molekuler belum dikatahui dengan jelas. Salah satu pendekatan yang dapat digunakan untuk mengetahui mekanisme pasak bumi sebagai obat tradisional yang bermanfaat mengatasi disfungsi ereksi adalah penambatan molekul. Penambatan melekul dilakukan dengan cara melihat interaksi ligand dengan reseptor. Ligand yang berasal dari pasak bumi adalah 5-methoxycanthin-6-one,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Docking score (Gibbs free energy) is a parameter to determine the strength of the ligand-receptor bond. If the value gets smaller (negative), the stronger the bond between the test ligand and the receptor [21]. The results from the molecular docking of alkaloid compounds against PLpro showed that Nigellidine had great strength to interact with the SARS-CoV-2 PLpro target receptor.…”
Section: Resultsmentioning
confidence: 99%
“…Docking score (Gibbs free energy) is a parameter to determine the strength of the ligand-receptor bond. If the value gets smaller (negative), the stronger the bond between the test ligand and the receptor [21]. The results from the molecular docking of alkaloid compounds against PLpro showed that Nigellidine had great strength to interact with the SARS-CoV-2 PLpro target receptor.…”
Section: Resultsmentioning
confidence: 99%
“…Some active compounds that are thought to have aphrodisiac activity are niloticin from the Eurycoma longifolia plant (Eurycoma longifolia Jack.) (Hadi et al, 2020), stigmasterol from purwoceng plant (Pimpinella alpina Molk) (Abdullah et al, 2021), protodioscin from rujak polo plant (Tribulus terrestris) (Maleki-Saghooni et al, 2020), Icariin from goat horn grass plants (Epimedium sp.) (Ganapathy et al, 2021), Yohimbine from yohimbe (Pausinystalia johimbe) plant (Brunetti et al, 2020) and ginsenoside from chinese ginseng plant (Panax ginseng Mayer) (Lin et al, 2022).…”
Section: Introductionmentioning
confidence: 99%